Challenges to Women's Adoption of the Human Papillomavirus Vaccine in India: An Updated Review - Brij Bhushan Sharma (International Journal of Vaccines, 2025)
The widespread availability of human papillomavirus (HPV) vaccines in some countries throughout the last ten years has demonstrated encouraging outcomes in reducing HPV infection and associated conditions including warts and precancerous lesions. We highlight vaccination coverage and efficacy in this study, which includes the most recent data on available HPV vaccinations. Furthermore, the topic of pan-gender immunisation and ongoing clinical trials is covered. Increasing vaccination coverage is now something that needs more work, particularly in low- and middle-income nations. One of the most important steps we can take is to raise awareness and educate people about HPV and the benefits of getting vaccinated. The next step in vaccine development is to create vaccinations that target HPV strains that are not covered by the ones that are currently available. Future research should monitor and assess all HPV-related cancers, including anal and head and neck cancers, particularly in nations that have implemented pan-gender immunisation initiatives. Further research on therapeutic vaccinations should be conducted in conjunction with other cancer treatments. HPV vaccine was introduced in India in 2008, when bivalent and quadrivalent vaccines were licensed. A nonavalent vaccine was licensed in 2018. The Serum Institute of India launched its first indigenous HPV vaccine, Cervavac, in January 2023.
Keywords: Cervarix; Cervavac; Gardasil; Gardasil 9; Human papillomavirus; Vaccine